Analisis Pandangan Siswa Terhadap Pola Interaksi Guru Ekonomi dalam Pembelajaran di Kelas Fase E-X SMAN 1 Bandar Lampung - Fayiz, Zidan Muhammad; Habiburrahman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to analyze students' perspectives on the interaction model of economics teachers in learning economics subjects in E-X phase classes at SMAN 1 Bandar Lampung. The research method used is qualitative method combined with descriptive analysis. Data were collected through observations, questionnaires, and documents. This study involved students from E-X classes and the school's economics teachers. Research results show that the majority of students rate from good to very good the form of interaction of economics teachers during the learning process. They view economics teachers as interactive by providing materials, answering questions clearly, and creating a comfortable learning atmosphere. However, some aspects received lower ratings, such as teachers' unfamiliarity with students' names. Based on the results, it is recommended to increase the interaction between economics teachers and students outside the classroom and strengthen the relationship between teachers and students. This will create a more productive and positive learning environment, as well as strengthen interpersonal relationships within the school environment. This study makes an important contribution to the understanding of interaction patterns between teachers and students in learning economics and provides appropriate suggestions to improve the quality of learning.